Implementasi Software Plagiasi dan Google Classroom Untuk Membantu Penilaian Tugas Siswa Pada SMK Nasional Berbah-Seleman - Hayaty, Mardhiya (Universitas Nusantara PGRI Kediri, 2020)
Work on student assignments and assessments are done manually so that evaluation cannot be done objectively because many tasks are similar or even the same as other student assignments. Copying other people's work is unlawful; students lack an understanding of the definition of plagiarism. Therefore education about this is done early, especially for the world of knowledge, which incidentally really appreciates the work of others. Making plagiarism software is needed to answer these challenges; this service activity provides training to teachers in managing online-based student assignments and checking assignment documents using plagiarism software. This activity can make it easier for teachers to offer assignment assessments and provide students with an understanding of the originality of a work.